Program Edukasi Masyarakat Dengan Edukasi Beserta Skrining Kadar Vitamin D Untuk Kesehatan Rambut Pada Lanjut Usia - Moniaga, Catharina Sagita; Sugiharto, Hans; Febriastuti, Abebi; Gunaidi, Farell Christian; Destra, Edwin; Firmansyah, Yohanes (STIKes Ibnu Sina Ajibarang, 2024)
Hair is an important aspect of a person's appearance. Hair in the elderly experiences a decline in quality which is often characterized by thinning, brittleness and loss. Vitamin D plays an important role in this condition because it affects the growth cycle of hair follicles. A deficiency can cause hair to become brittle and fall out easily. In this community service activity, education is provided to explain the importance of vitamin D and how to get it through a healthy diet and lifestyle. Screening using a hair analyzer shows problems with hair loss and low hair density as well as lots of dead skin cells. Effective education and nutritional interventions, including vitamin D supplementation, are essential to improve hair health and ultimately the quality of life of elderly. Treating vitamin D deficiency, including hair and scalp care, must be an integral part of the elderly's health program. Keywords: education, hair health, elderly, community service, vitamin D